2019
DOI: 10.1039/c8lc01223g
|View full text |Cite
|
Sign up to set email alerts
|

Self-digitization chip for quantitative detection of human papillomavirus gene using digital LAMP

Abstract: Digital nucleic acid amplification and detection methods provide excellent sensitivity and specificity and allow absolute quantification of target nucleic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…In recent years, droplet-based microfluidic devices have been widely applied in the absolute quantification of nucleic acids with digital PCR/LAMP techniques, 37, 38 such as self-digitalization (SD) LAMP chip, 39, 40 interfacial printing system, 22 and centrifugal micro-nozzle array. 24 Besides, many commercial systems emerge as research tools.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, droplet-based microfluidic devices have been widely applied in the absolute quantification of nucleic acids with digital PCR/LAMP techniques, 37, 38 such as self-digitalization (SD) LAMP chip, 39, 40 interfacial printing system, 22 and centrifugal micro-nozzle array. 24 Besides, many commercial systems emerge as research tools.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off value was defined as reported previously. (Kreutz et al, 2019) The calculation of copy numbers based on the Poisson statistics was described previously. (Shen et al, 2010) For all digital LAMP experiments, if there were fewer than three positive wells per device, then the experiments were determined to be negative.…”
Section: Digital Lamp On Sp-slipchipmentioning
confidence: 99%
“…Different microwell and microchamber designs were developed to compartmentalize liquid in small volumes. (Heyries et al, 2011;Kreutz et al, 2019;Ottesen et al, 2006;Zhou et al, 2019) Microfluidic devices with the features of co-flow, crossflow, and flow focusing were demonstrated to reliably form liquid droplets with high throughput. (Hindson et al, 2011;Nie et al, 2019;Zeng et al, 2013;Zhang et al, 2015a) In addition, approaches with mechanical dispensing or agitation (Jiang et al, 2016;Zhu et al, 2015) and centrifugal force (Chen et al, 2017) have been demonstrated to form droplets with good uniformity and high throughput.…”
Section: Introductionmentioning
confidence: 99%
“…The system could detect HBV (hepatitis B virus)-DNA at a concentration of 1 × 10 1 to 1 × 10 4 copies/µL. The LED-driven digital LAMP chip and the integrated device; therefore, demonstrate high accuracy and excellent performance for the absolute quantification of low-abundance nucleic acids, showing the advantages of integration, miniaturization, cost, and power consumption.Micromachines 2020, 11, 177 2 of 15 Studies on dNAAT have focused on sample segmentation using innovative microfluidic chips [7][8][9]. Although the microfluidic chips for dNAAT have emerged endlessly, most dNAAT instrument systems still require more than three sets of auxiliary devices, including sample segmentation unit, heating unit and fluorescence detection unit.…”
mentioning
confidence: 99%
“…Micromachines 2020, 11, 177 2 of 15 Studies on dNAAT have focused on sample segmentation using innovative microfluidic chips [7][8][9]. Although the microfluidic chips for dNAAT have emerged endlessly, most dNAAT instrument systems still require more than three sets of auxiliary devices, including sample segmentation unit, heating unit and fluorescence detection unit.…”
mentioning
confidence: 99%